Hair growth-promotion effects and antioxidant activity of the banana flower extract HappyAngel®: double-blind, placebo-controlled trial - Chia-Hua Liang; Yung-Hsiang Lin; Yung-Kai Lin; Chi-Fu Chiang (Food Science and Human Wellness)
Banana flowers contain various bioactive components, including several antioxidants with anti-inflammatory effects. However, it is unclear whether they can reduce and prevent hair loss. This study examines the effect of banana flower extracts on preventing hair loss and strengthening hair roots. The banana flower extract (HappyAngel®) was used to treat human hair follicle dermal papilla cells (HFDPCs) and the expression of reactive oxygen species (ROS), dihydrotestosterone (DHT), and hair-related genes (SRD5A1, SRD5A2, AR, and KROX20) were monitored. Fifty subjects were divided into a placebo group and a banana flower group. The experimental group consumed banana flower extract daily for twelve weeks and then underwent hair testing, hair-related genes analysis, collection of hair loss, and questionnaires. The results showed that the banana flower extract significantly increased hair cell growth and decreased the expression of ROS, DHT, and hair follicle growth inhibition-related SRD5A1, SRD5A2, and AR genes, and significantly increased the expression of hair growth-related KROX20 gene in HFDPCs. Consuming banana flower extract for twelve weeks increased the hair root diameter and reduced hair loss and scalp redness compared to the placebo group. Thus, banana flower extract (HappyAngel®) can stimulate hair growth and inhibit the activation of hair loss genes.